Mechanistic study on the alleviation of postmenopausal osteoporosis by Lactobacillus acidophilus through butyrate-mediated inhibition of osteoclast activity - Junjie Dong; Guizhao Shu; Jin Yang; Bing Wang; Lingqiang Chen; Zhiqiang Gong; Xiaofeng Zhang (Scientific Reports, 2024)
Abstract In China, traditional medications for osteoporosis have significant side effects, low compliance, and high costs, making it urgent to explore new treatment options. Probiotics have demonstrated superiority in the treatment of various chronic diseases, and the reduction of bone mass in postmenopausal osteoporosis (PMOP) is closely related to the degradation and metabolism of intestinal probiotics. It is crucial to explore the role and molecular mechanisms of probiotics in alleviating PMOP through their metabolites, as well as their therapeutic effects. We aim to identify key probiotics and their metabolites that affect bone loss in PMOP through 16srDNA sequencing combined with non-targeted metabolomics sequencing, and explore the impact and possible mechanisms of key probiotics and their metabolites on the progression of PMOP in the context of osteoporosis caused by estrogen deficiency. The sequencing results showed a significant decrease in Lactobacillus acidophilus and butyrate in PMOP patients. In vivo experiments confirmed that the intervention of L. acidophilus and butyrate significantly inhibited osteoclast formation and bone resorption activity, improved intestinal barrier permeability, suppressed B cells, and the production of RANKL on B cells, effectively reduced systemic bone loss induced by oophorectomy, with butyric acid levels regulated by L. acidophilus. Consistently, in vitro experiments have confirmed that butyrate can directly inhibit the formation of osteoclasts and bone resorption activity. The above research results indicate that there are various pathways through which L. acidophilus inhibits osteoclast formation and bone resorption activity through butyrate. Intervention with L. acidophilus may be a safe and promising treatment strategy for osteoclast related bone diseases, such as PMOP.